On the topology and the boundary of N-dimensional RCD(K,N) spaces - Kapovitch, V; Mondino, A (Mathematical Sciences Publishers, 2021)
We establish topological regularity and stability of N-dimensional RCD(K,N) spaces (up to a small singular set), also called non-collapsed RCD(K,N) in the literature. We also introduce the notion of a boundary of such spaces and study its properties, including its behavior under Gromov-Hausdorff convergence.